Brucellar cervical epidural abscess - A rare cause of neck pain. (2021) - Baghi, Mohamed abdunasser M.; Al-Aani, Fuad Khalil; Rahil, Ali; Ayari, Basma
Abstract: Brucellosis, is a zoonosis infection with a planetary distribution, caused by facultative intracellular bacteria of the genus Brucella, thus has a variable clinical presentation. Spinal epidural abscesses are a rare presentation of the disease, and may carry risk of a neurovascular compromise. Here we report a 22-year-old male with spinal brucellosis complicated by a cervical epidural abscess. The diagnosis was based on presenting symptoms and his occupation, confirmed by laboratory investigations, blood culture and magnetic resonance imaging results. Surgical drainage of abscess was performed, followed by 6 weeks of combination antibiotic therapy. The combination of the therapeutic strategies we used lead to a significant clinical improvement in this rare case.